The Application of Analytical Hierarchy Process (AHP) to Determine Best Cost Efficiency Program: A Case Study of Green Farm Company - Wijaya, Fajar Palguna; Siallagan, Manahan Parlindungan Saragih (Penerbit Goodwood, 2025)
Purpose: CV. XYZ as hydroponic agriculture, for years since 2019, producing high-demand crops such as lettuce and spinach. Nevertheless, there has been a decline in revenue that is a result of the inefficiencies in the management of operational costs. Thus, this study aimed to come up with identification and prioritization of cost-efficiency strategies with the intervention of in-depth interviews and Analytical Hierarchy Process (AHP). Method: A mixed-mode methodology was used. The qualitative in-depth interviews between the Board of Directors were analyzed for the most important triangulated criteria and subcriteria that drive operational efficiency. A quantitative AHP analysis was done to slightly compare these factors. Results: Technology Levers turned out to be the most influent factor, hybrid farming system was the most feasible alternative, with advantages for offering a balanced system that integrates traditional farming practices with modern technologies for sustainability and efficiency. Conclusions: Integrating human capital development and technological innovation is imperative for optimal operation efficiency and sustainable growth in the hydroponic agriculture sector. Limitations: This research is limited by the scope of its data sources and the relatively short evaluation period, which may not fully capture the long-term impacts of the proposed strategies. Contributions: This conclusion contributes to the field by offering a strategic framework that integrates technological innovation and human resource development for improved agricultural productivity. It provides policymakers, agribusiness leaders, and practitioners with actionable insights into balancing traditional knowledge and digital transformation to address systemic inefficiencies.